Preclinical Review of the Antidiarrheal Potential Herbal Plants: Kajian Potensi Antidiare Tanaman Herbal secara Praklinik - Arief, Maryam Jamila; Robin, Yosepha Vania Usun; Sheila, Annieza; Bidang, Diani Kristiani; Dewi, Jingga Apriani Jevita; Wijayanti, I Dewa Ayu Made Dwita; Rahmadania, Siti Nur (Jurnal Riseta Naturafarm, 2026)
Diarrhea remains a major gastrointestinal health problem, highlighting the need for safe and effective alternative therapies, including those derived from traditional medicinal plants. This review aims to evaluate the antidiarrheal potential of various medicinal plants based on preclinical evidence. A narrative review approach was employed by searching the Google search engine using the keyword “antidiarrheal” for scientific publications published between 2018 and 2025. The included literature consisted of preclinical studies using in vivo and/or in vitro approaches. The medicinal plants reviewed included Piper betle L., Eugenia polyantha, Zingiber officinale, Mangifera indica, Psidium guajava L., Curcuma longa L., Pithecellobium jiringa, Crescentia cujete L., fermented Hylocereus polyrhizus, Centella asiatica, Pometia pinnata, Moringa oleifera L., Strobilanthes crispus, and Cuminum cyminum. The findings indicate that these plants exhibit antidiarrheal activity through multiple mechanisms, including antibacterial effects against enteric pathogens, inhibition of intestinal motility, antispasmodic effects, and reduction of intestinal fluid secretion, which are closely associated with the presence of secondary metabolites such as flavonoids, tannins, alkaloids, terpenoids, and phenolic compounds. Several plants demonstrated antidiarrheal efficacy comparable to loperamide at specific doses, suggesting their potential as alternative antidiarrheal agents. However, further studies involving extract standardization, identification of active marker compounds, safety evaluation, and clinical trials are required to confirm their efficacy and safety in humans.